The Role of Nurses in Patients with Intra-aortic Balloon Pump: Involvement, Understanding, and Management of the Patient’s Comfort - Rasaria, Shweta; Sawant, Suchita (Innovational: Journal of Nursing and Healthcare, 2024)
Health is pivot on which the man’s whole personality and its well-being depend. Coronary artery serves as a fuel pipelines to the heart muscles. Intra-aortic balloon pump (IABP) is considered as the first hemodynamic support device to help in improvements in the myocardial oxygen supply/demand ratio and circulatory support. It remains the most widely used mechanical cardiac support device due to its simplicity, ease of insertion, and long clinical track record. To achieve the best possible outcome for a patient managed with IABP, nursing and medical staff required specialized skills. Nurses play a crucial role in caring patient with IABP. Nurses who care for patients managed with IABP require knowledge of the mechanism and actions of this therapeutic device. Cardiovascular nurses are caring for these patients requiring skills and knowledge that enable prompt recognition and treatment of sometimes life-threatening complications associated with balloon pump therapy. To gain a greater understanding of IABP therapy, nurses should become familiar with specific institutional policies regarding operation of this device. The critical care nurse needs to be aware of various factors to adequately assess for and ensure optimal IABP performance.